1997
DOI: 10.1021/jp952465v
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Predictions of Second-Order Hyperpolarizabilities of Metallocenes

Abstract: The geometries in the staggered and eclipsed conformations of the metallocenes, M(C5H5)2 with M = Mn, Fe, Co, Ni, and Ru, have been calculated at the local and nonlocal density functional theory (LDFT and NLDFT) levels. The M−C distance is predicted to be too short at the LDFT level and too long at the NLDFT level. The doublet low-spin states for M = Mn and Co show distortions away from the idealized fivefold symmetries. The low-spin state for M = Mn is predicted to be lower in energy than the high-spin state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 51 publications
7
58
6
Order By: Relevance
“…Matsuzawa et al [46] using DFT and Waite et al [35] employing the CHF-PT-EB-CNDO method found for the second hyperpolarizability 5.67 10 À36 esu and 4.10 10 À36 esu, respectively. Ghosal et al [34] employing DFWM found a value of (16.12 AE 1.8) 10…”
Section: Semiempirical Calculations Of the Second Hyperpolarizabilitymentioning
confidence: 98%
“…Matsuzawa et al [46] using DFT and Waite et al [35] employing the CHF-PT-EB-CNDO method found for the second hyperpolarizability 5.67 10 À36 esu and 4.10 10 À36 esu, respectively. Ghosal et al [34] employing DFWM found a value of (16.12 AE 1.8) 10…”
Section: Semiempirical Calculations Of the Second Hyperpolarizabilitymentioning
confidence: 98%
“…Cobaltocene has been subject of wide research [3,4,22,34,52,58,74,80], but only recently a detailed analysis [86] of the JT distortion has been carried out. Calculations were done for both the eclipsed and the staggered conformations, giving similar results.…”
Section: Cobaltocenementioning
confidence: 99%
“…As a particular example, we use bis(cyclopentadienyl)cobalt(II) (cobaltocene), a metallocene with a d 7 electronic configuration, which has been a matter of extensive research for years [14][15][16][17][18][19][20][21]. The distortion of cobaltocene is discussed qualitatively using group theory arguments, and the potential energy surface is calculated by a simple computational recipe [11], using vibronic coupling.…”
Section: Introductionmentioning
confidence: 99%